Development of resilience model in people with human immunodeficiency virus undergoing antiretroviral therapy - Lailiah, Novianti; Nursalam, Nursalam; Indarwati, Retno (International Journal of Public Health Science (IJPHS), 2024)
Resilience that has not been formed and self-regulatory functions that are not optimal, play a role in low adherence to treatment for people living with HIV/AIDS (PLHIV). This study aimed to develop a resilience model of antiretroviral therapy (ARV) adherence and quality of life for PLHIV. This study used a cross-sectional approach to 185 PLHIV in Tulungagung, East Java, Indonesia who were selected using simple random sampling. Individual factors, disease representation, emotional response, social support, interpretation, coping, resilience, adherence, and quality of life were variables in this study that were measured using a questionnaire. The data were then analyzed descriptively and using structural equation model (SEM) based on partial least square (PLS). The results showed that individual factors (T=4.062), disease representation (T=3.755), emotional response (T=3.988), and social support (T=2.753) affected interpretation of disease. Interpretation of disease then influences coping (T=5.285). Coping affects resilience (T=4.045), resilience influences ARV adherence (T=2.846), and adherence affects quality of life (T=10.050). Other factors that directly influence ARV adherence are emotional response (T=3.120) and social support (T=3.255). This resilience model is relevantly able to improve adherence in PLHIV. Emotional response is a factor that has the strongest influence in shaping the resilience of PLHIV in the mechanism of adherence and quality of life.